Angioimmunoblastic T-cell lymphoma (AITL): a rare entity, commonly misdiagnosed - Seman, Zainina; Omar, Mohd. Shah Fazly; Mohd Tajuddin, Syirah Nazirah (Universiti Putra Malaysia, 2024)
Angioimmunoblastic T-cell lymphoma (AITL) presents a wide range of clinical and histopathological features, often resembling various reactive and neoplastic diseases. This similarity poses a challenge in making a definitive diag-nosis in many cases. Distinguishing the neoplastic T cells can be particularly difficult since they typically constitute a small proportion of the overall cellular infiltration. The tumour and inflammatory cells exhibit polymorphism and variable proportions. Additionally, the concurrent proliferation of B cells can mimic both reactive and neoplastic conditions. Furthermore, the atypical B cells may resemble Reed-Sternberg cells and show positivity for CD30 and CD15, often leading to misdiagnosis as classical Hodgkin lymphoma. In this case report, we present the case of a 65-year-old man initially diagnosed with classical Hodgkin lymphoma who underwent ABVD chemotherapy. Upon experiencing symptoms of disease relapse, the diagnosis was revised to AITL.